1997
DOI: 10.1093/oxfordjournals.aje.a009107
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Patches in Smoking Cessation: A Randomized Trial among Over-the-Counter Customers in Denmark

Abstract: The authors examined the effect of 24-hour nicotine patches in smoking cessation among over-the-counter customers in Denmark, based on a randomized double-blind placebo-controlled trial. Participants were consecutive customers to whom nicotine patches were offered as the only treatment. Forty-two pharmacies in the areas of Aarhus and Copenhagen in Denmark participated in the trial, and 522 customers who smoked 10 or more cigarettes per day were randomized to either nicotine patches or placebo from January to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 33 publications
1
93
0
3
Order By: Relevance
“…Smokers may intuitively understand that there is little point in continuing patch treatment if they fail to stop early on, in keeping with findings that smoking within the first week of attempted cessation predicts later failure to quit. 7,[18][19][20] Intermittent use may also be the result of improper instruction or inadequate provider counseling. However, in this study, all participants attended a session with research staff where they were instructed in proper use of the patch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smokers may intuitively understand that there is little point in continuing patch treatment if they fail to stop early on, in keeping with findings that smoking within the first week of attempted cessation predicts later failure to quit. 7,[18][19][20] Intermittent use may also be the result of improper instruction or inadequate provider counseling. However, in this study, all participants attended a session with research staff where they were instructed in proper use of the patch.…”
Section: Discussionmentioning
confidence: 99%
“…Swartz et al, 6 surveying nicotine patch users identified through pharmacy records, showed that persons who used patch daily (as opposed to less frequently) were more likely to be abstinent during patch use, and had 1.6 greater odds of successfully quitting 9 to 12 months later. Sonderskov et al 7 reported that among pharmacy customers in Denmark, adherence to free nicotine patch was 45%, 33%, and 38% at 4, 8, and 12 weeks, respectively, among motivated smokers, and did not differ according to treatment dose. Even when the patch is used, smokers often continue to smoke.…”
mentioning
confidence: 99%
“…There were two alcohol interventions, 46,48 12 smoking cessation interventions, 44,45,[49][50][51][52][53][55][56][57][58][59][60]63 five weight-loss interventions 39,[64][65][66][67] and five multicomponent interventions that included pharmacotherapy and lifestyle changes in participants with comorbidities including dyslipidaemia (n = 1 study), 71 hypertension 72 and type 2 diabetes mellitus (n = 3 studies). [68][69][70] Four studies had multiple publications, one smoking cessation study had an English 63 and a Danish 73 publication; another smoking cessation study 49 had two additional publications including a paper on cost-effectiveness 51 and a paper on shorter-term follow-up. 50 Another smoking cessation study 60 had an additional publication on cost-effectiveness.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A recaída deve ser vista diferente do "slip" ou "escorregada", ocasião em que o participante pode "dar uma tragada" aleatória, não se configurando volta à adicção (Sonderskov et al, 1997;Presman et al, 2005).…”
Section: íNdice De Sucesso E Dados Sócio-demográficosunclassified
“…Na verdade, não sabia quem eu seria, sem o cigarro na mão". Quando o fumante fica pelo menos um ano abstinente, passa a ser considerado como tendo tido sucesso total no tratamento (Sonderskov et al, 1997;Presman et al, 2005). Assim sendo, nesta amostra, o período de abstinência de pelo menos dez meses e a constatação de que alguns participantes do grupo conseguiram ficar um ano sem fumar, é um resultado muito promissor.…”
Section: íNdice De Sucesso E Dados Sócio-demográficosunclassified